ANALISIS HUBUNGAN STRATEGI BISNIS, MODEL PENGUKURAN KINERJA, KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN (STUDI EMPIRIS PADA INDEKS ISLAM JAKARTA) - Eko Hariyanto (BAJ: Behavioral Accounting Journal, 2019)
This study aims to obtain empirical evidence about the relationship between corporate strategy, performance measurement model, company performance and value of the firm. The research subjects are companies that have gone public and entered the Jakarta Islamic Index in 2013 until 2017. The number of samples in this study were 30 companies. By using path analysis in analyzing data, it is known that the results of this study, it can be concluded that value of the firm is directly influenced by the variable corporate performance and performance measurement model. The cost leader strategic variable influences the corporate performance and performance measurement model variables, while the product deferencial strategic directly influences corporate performance. It is hoped that this research will be used as a basis for decision making about the company's strategy and its performance measurement model.